External loading does not change energy cost and mechanics of rollerski skating - Millet, G.; Perrey, St.; Candau, R.; Belli, A.; Borani, F.; Rouillon, J. D. (European Journal of Applied Physiology, 1998)
External loading up to 12% body mass ( mb) does not increase storage and release of elastic energy of lower limb muscles during SSC in roller ski skating.